Right Sided Bochdalek Hernia in Adult: A Case Report & Review of Literature - Sharma, Bishownath; Gupta, Dipesh (Nepalese Journal of Radiology, 2018)
Bochdalek hernia is the most common congenital diaphragmatic hernia that typically presents in childhood. However, right sided diaphragmatic hernia is relatively rare. We review the case of 21 years old female with incidentally detected congenital diaphragmatic hernia on the right side. There are fewer than 20 cases of right sided diaphragmatic hernia reported in adults in literature.